Oral glucosamine sulfate supplementation does not induce endoplasmic reticulum stress or activate the unfolded protein response in circulating leukocytes of human subjects - McAlpine, Cameron S.; Beriault, Daniel R.; Behdinan, Tina; Shi, Yuanyuan; Werstuck, Geoff H. (Canadian journal of physiology and pharmacology, 2014)
Glucosamine sulfate is a dietary supplement that is marketed as a treatment for osteoarthritis. Recent evidence from animal and cell culture models have suggested that glucosamine treatment can promote the misfolding of proteins and the activation of the unfolded protein response (UPR). We investigated whether glucosamine sulfate supplementation activates the UPR in circulating leukocytes of human subjects. Cultured Thp1 human monocytes were exposed to increasing concentrations of glucosamine (0, 0.25, 1.0, 4.0 mmol·L –1 ) for 18 h. We observed a dose-dependent increase in intracellular glucosamine levels as well as the activation of UPR. To test the effect of glucosamine sulfate supplementation in humans, 14 healthy human subjects took 1500 mg·day –1 glucosamine sulfate for 14 days. Metabolic parameters and blood samples were collected before and after supplementation. In humans, glucosamine sulfate supplementation did not alter metabolic parameters including lipid levels and glucose tolerance. Further, glucosamine sulfate supplementation did not affect intracellular glucosamine levels or activate the UPR in the leukocytes of human subjects. Our results indicate that in healthy human subjects, the recommended dose of glucosamine sulfate (1500 mg·day –1 ) for 14 days does not significantly alter intracellular glucosamine levels and does not activate the UPR in circulating leukocytes.